Bacterial Biofilms and Ethylenediamine-N,N’-disuccinic acid (EDDS) as Potential Biofilm Inhibitory compound: EDDS as biofilm inhibitory compound - Kumari, Nimerta; Rathore, Shabnam; Patoli, Bushra Bano; Patoli, Atif Ahmed (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2020)
Bacterial biofilms are populations of microorganisms that stick to some surfaces and are embedded in self-secreted extracellular polymeric matrixes. These synergistically controlled sessile cells exhibit different proteome than their planktonic counterpart and are often difficult to treat. They make a different mechanism to escape the antimicrobial activity and host defenses. Biofilms on indwelling prosthetic devices are a major problem in the medical field because they could lead to recurrent and systemic infections. Biofilms also result in bio-corrosion in industries and their remediation often causes environmental problems. The goal of this study is to find antimicrobial and biofilm inhibition activity of non-toxic and biodegradable economical iron-chelating compound EDDS against Staphylococcus aureus SA113 and Pseudomonas aeruginosa PAO1 strains. Broth microdilution assay was performed to find the inhibitory concentration of EDDS and biofilm assay performed in the micro-well plate to determine the biofilm inhibitory concentration of EDDS against SA113 and PAO1. The results show that a higher concentration of EDDS is required to suppress the growth of SA113 a gram-positive bacterium compare to gram-negative PAO1 strain. EDDS successfully inhibited the biofilm formation of both SA113 and PAO1 at very low concentration and significant biofilm inhibition (p<0.05) was observed at 0.78 mM and 1.56 mM EDDS concentration for PAO1 and SA113 respectively. Biodegradable ion-chelator EDDS is a good biofilm inhibitor compound for both S. aureus SA113 and P. aeruginosa PAO1 strains.